Transformative Use of Additive Technology in Design and Manufacture of Hydraulic Actuator for Fly-by-Wire System - Krzysztof Warzocha; Jerzy Szura; Piotr Bąk; Paweł Rzucidło; Tomasz Rogalski (Applied Sciences, 2021)
In this paper, the results of research on additively manufactured aerospace parts made of maraging steel are presented. This state-of-the-art technology seems to have the highest potential for practical use in the field of ultra-light and high-performance aerospace hydraulic parts. The strength properties of representative specimens made with steel 1.2709 were investigated. The researchers conducted static tensile testing, fatigue tensile testing, and pressure impulse testing. A Goodman diagram was plotted to visualize the impact of the building orientation vs. load character on the fatigue strength of the additive manufacturing (AM) specimens. Based on the research carried out on the strength of the AM samples, an aircraft flight control actuator was designed to achieve the highest level of safety integrity along with the greatest simplicity and lowest weight relative to hydraulic actuators manufactured using classical methods. The entire design process was integrated with the manufacturing process to achieve this target.